CHILDREN, GENDERS AND SEXUALITIES: ETHICAL-POLITICAL IMPLICATIONS OF PARENTALITIES - Souza, Leonardo Lemos de [UNESP]; Salgado, Raquel Gonçalves; Mattos, Amana Rocha (Universidade Estadual de Maringa, 2022)
In dialogue with scenes from the Brazilian context of sexual and gender policies and based on feminist and queer studies, the article aims to outline lines and flows of thought about the tensions between parental relationships and the right of children to their expressions of genders and sexualities. For this, it situates childhood as a device of biopolitics that is intertwined with the devices of genders and sexualities in the models outlined by psychological and educational narratives. Then, it discusses the presence of familism in public policies for families in Brazil in which anti-gender discourses seek to affirm a hegemonic model of family, as the place that safeguards heteronormativity and cisgenerity. It ends by outlining the field of tensions over the relationships between adults and children, which emerge from the previous sections, seeking arguments for epistemic and ethical-political positions of parenting.
INFANCIAS, GÉNERO Y SEXUALIDADES: IMPLICACIONES ÉTICO-POLÍTICAS DE LAS PATERNIDADES
INFÂNCIAS, GÊNEROS E SEXUALIDADES: IMPLICAÇÕES ÉTICO-POLÍTICAS DAS PARENTALIDADES
Keywords: Childhoods; Genders and sexualities; Parenting